(untitled) (Strathmore Law Journal, 2025)
It is now widely acknowledged that formal law is limited. This is particularly in contexts where: 1) the law permits the coexistence of different legal orders, and 2) there exist juridical norms that have a greater appeal compared to the formal norms. This limitation of formal law has especially been evidenced in the modern and democratised era of international environmental law and policy. For this reason, interest has been sparked regarding other informal norms, such as ethics and belief and value systems, that can be leveraged in environmental governance. Furthermore, the limitation has raised questions about the actors that will participate in the formulation of these informal norms. Based on the foregoing, this study seeks to investigate the role children, and the youth can play in shaping ethics, beliefs and customs for plastic governance in Africa. Employing the Narrative Policy Framework, the study makes the argument that children and the youth in Africa have the capacity to frame persuasive narratives which could mould ethics, beliefs and customs to the advantage of plastic governance in Africa.